2013
DOI: 10.5433/2236-6407.2013v4n1p2
|View full text |Cite
|
Sign up to set email alerts
|

A percepção do paciente sobre adesão à medicação antidepressiva

Abstract: ResumoBusca-se, no presente estudo, compreender qual a percepção do profissional de saúde sobre o fenômeno da não adesão à medicação, quando está no lugar de paciente. Os participantes foram profissionais da área da saúde de um hospital de referência na cidade de São Paulo que estavam sendo atendidos no Setor de Medicina do Trabalho, e que tinham indicação médica de tratamento com antidepressivos. Utilizou-se o método clínico-qualitativo, sendo a coleta de dados realizada por meio de entrevistas semidirigidas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A study made by Capela et al [39] observed a negative correlation between quality of life and bodily pain, anxiety and depression, indicating that the more severe the symptoms, the worse the quality of life. The presence of depressive symptoms resulted in greater absenteeism, lower productivity and worse quality of life for patients [40]. According to Berber et al [37], depression has a negative effect on quality of life because it exacerbates feelings of pain and physical impairment, making treatment adherence more difficult and compromising social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A study made by Capela et al [39] observed a negative correlation between quality of life and bodily pain, anxiety and depression, indicating that the more severe the symptoms, the worse the quality of life. The presence of depressive symptoms resulted in greater absenteeism, lower productivity and worse quality of life for patients [40]. According to Berber et al [37], depression has a negative effect on quality of life because it exacerbates feelings of pain and physical impairment, making treatment adherence more difficult and compromising social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…There is, in the statements, nuisance arising from the use of large amounts of medication for a long period of time. Allusive to this, the literature indicates that the time and complexity of treatment may interfere in the values attributed to the disease and are able to develop negative feelings about the therapeutic project [19][20].…”
Section: E3mentioning
confidence: 99%